2016
DOI: 10.1016/j.immuni.2015.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenic Chemotherapy Sensitizes Tumors to Checkpoint Blockade Therapy

Abstract: SUMMARY Checkpoint blockade immunotherapies can be extraordinarily effective, but may benefit only the minority of patients whose tumors are pre-infiltrated by T cells. Here, using lung adenocarcinoma mouse models, including genetic models, we show that autochthonous tumors that lacked T cell infiltration and resisted current treatment options could be successfully sensitized to host antitumor T cell immunity when using appropriately selected immunogenic drugs (e.g. oxaliplatin combined with cyclophosphamide f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
693
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 807 publications
(730 citation statements)
references
References 44 publications
28
693
8
1
Order By: Relevance
“…31 The induction of immunogenic conditions in the TME with an immunogenic chemotherapy or radiation therapy is thought to convert immunologically “cold” tumors into “hot” tumors via release of tumor neoantigens. 32,33 Similarly, the pushing of tumor cells toward immunogenic death by SGT-53 may be quite effective in promoting in tumor elimination by the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…31 The induction of immunogenic conditions in the TME with an immunogenic chemotherapy or radiation therapy is thought to convert immunologically “cold” tumors into “hot” tumors via release of tumor neoantigens. 32,33 Similarly, the pushing of tumor cells toward immunogenic death by SGT-53 may be quite effective in promoting in tumor elimination by the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, assuming that vascular normalization did not occur in metronomic chemotherapy, the efficacy of treatment would be better than that of MTD owing to reduced immunogenic cell death and the decreased number of Tregs as a result of metronomic dose scheduling (SI Appendix, Fig. S12) (41).…”
Section: Dose Scheduling and Time For Tumor Relapse Determine Treatmentmentioning
confidence: 99%
“…14 , 15 Similarly, it has been shown that immunogenic cell death (ICD) inducers such as oxaliplatin and cyclophosphamide sensitize KRAS-induced lung cancers to subsequent immune checkpoint blockade. 16 It is not unreasonable to postulate that viruses, in particular T-VEC, can induce ICD because T-VEC has been genetically modified to remove genes that suppress the immune response and accentuate the premortem stress responses, including the type-1 interferon response, that characterize ICD. 17-22 These emerging studies emphasize the need to rationally design for combination immunotherapies with respect to timing and dosing.…”
mentioning
confidence: 99%